Mediatorship Office as an Alternative Dialogue to Indonesian Muslim: An Exercise to the Christology of John Owen - Christar Arstilo Rumbay; Handreas Hartono (Sekolah Tinggi Theologia Abdiel, 2021)
Christology receives less attention as a topic of dialogue to other faith due it contains fluctuation. Indeed, Christology serves the possibility to bridge contributive discussion to faith. This essay is a systematic interreligious study that attempts to evaluate the mediatorship of Christ. The expectation is, this treatise could offer alternative dialogue to Indonesian Muslims. The knowledge of John Owen leads this treatise to gain several notions concerning the mediatorship of Christ that may help Christian to renovate better life for Muslims in Indonesia. The unconditional and initiative love is the main attribute of mediatorship work that shares the possibility for dialogue with Indonesian Muslims.